ChemInform Abstract: Structural Evolution from 0D Units to 3D Frameworks in Pb Oxyhalides: Unexpected Strongly Corrugated Layers in Pb7O6Br2. Issue 7 (January 2016) - Siidra, Oleg I.; Gogolin, Mathias; Lukina, Evgeniya A.; Kabbour, Houria; Bubnova, Rimma S.; Mentre, Olivier; Agakhanov, Atali A.; Krivovichev, Sergey V.; Colmont, Marie; Gesing, Thorsten
Abstract: Single crystals of the new compound Pb7 O6 Br2 are prepared by solid state reaction of PbBr2 and α‐PbO (Pt crucible, 750 °C, 1 h).